Studies on the Short- and Long-Term Effects of Rubber-Canna Agroforestry Through Soil Analysis and a Metagenomic Approach - Sasaerila, Hidayat Yorianta; Effendi, Yunus; Wijihastuti, Risa Swandari; Pambudi, Arief; Nicola, Flavia De (Universitas Negeri Semarang, 2024)
Agroforestry combines trees and crops for sustainable benefits. We explore rubber and canna integration into agroforestry, emphasizing sustainability, biodiversity, and carbon sequestration. This study assesses C. indica's viability beneath 7-8-year-old rubber plantations, examining its impact on soil, microbial communities, and latex production. The research site in Subang, Indonesia, features, at the beginning, six-year-old rubber trees with variations in sunlight under canopies. Wild C. indica rhizomes from Mid Java are planted beneath rubber trees and open ground. No significant difference was found in plant height, rhizome weight, leaf area, number of leaves, r/s ratio, SLA, LWR, and LAR between C. indica cultivated beneath rubber trees (RC agroforestry) and on open ground. Although not significant, RC soil had higher N, P, K, and organic C levels than rubber monoculture (RM) soil two years after adopting the rubber-canna agroforestry system. After six years, RC soil had a greater pH, C, N, P, and K, clay and silt content, and Shannon E index than RM soil. Analysis of soil metagenomics showed the phylum Proteobacteria dominates and enhances soil fertility, particularly in RC soils. These results increase latex output at the RC site over the RM location. In conclusion, the Rubber-Canna agroforestry system enhances sustainability, soil fertility, and crop yield, addressing food security and environmental concerns. The primary novelty of this six-year study lies in the integration of C. indica into Southeast Asia's rubber agroforestry systems, highlighting its unique characteristics such as low-light survival, which can contribute to food security and soil protection.